Validation of Transcutaneous Bilirubinin Comparison with Serum Bilirubin for the Detection of Hyperbilirubinemia in Neonates - Sadeghian 1, Afsaneh; Neymati 2, Ghazale; Zolfaghari 2, Pouneh; Yahyaei 3, Elahe; Mirghasemi 3, Mehrisadat; Sohrabi 2*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2018)
Background: Neonatal hyperbilirubinemia is a common and dangerous complication that should be diagnosed as soon as possible.This study aimed to validate transcutaneous bilirubin in comparison with serum bilirubin for the detection of hyperbilirubinemiain neonates.Methods: This cross-sectional study was conducted in 280 infants with jaundice who were referred to Bahar Hospital in Shahroud in 2016. The serum bilirubin was measured by the photometric method. Three measurements of transcutaneous bilirubin were performed (by Bilichek) for each infant, and their average was recorded. The sensitivity and specificity of transcutaneous bilirubin measurements were assessed in comparison with the measurements using laboratory methods as the gold standard using ROC analysis.Results: Of the 280 neonates, 153 (54.6%) were male. The mean age of the patients was 11.77 ± 4.6 days. The mean bilirubin level was 16.9 ±10.1 mg/dl measured usingthe BiliChek method and 15.3 ± 9.5 mg/dl using the laboratory method, and the difference was significant (p<0.04). The sensitivity and specificity of the BiliChek measurements in neonates were 88.3% and 73.6%, respectively. According to the findings from the ROC curve, the cut off point was determined to be more than 14.7 units (surface area below the curve (AUC) = 87.5%).Conclusion: The results of this study showed that the accuracy (sensitivity and specificity) of the BiliChek device was good and can be used to measure the neonatal bilirubin.